To Share or Not to Share? Professional Norms, Reference Groups, and Information Withholding Among Life Scientists - Haas, Martine R.; Park, Sangchan (Organization Science, 2010)
Why do scientists withhold information from colleagues, violating the professional norm of sharing? Norm violations are usually attributed to individual interests that lead scientists to reject professional norms. In contrast, we take the view that norm violations can occur when professional norms are valued but it is difficult to ascertain the appropriate course of professional conduct. This view suggests that scientists may look to cues from their professional reference groups to resolve sociological ambivalence arising from conflicting role expectations. We analyze a data set of 1,251 geneticists and other life scientists from 100 U.S. universities and find that beyond individual-level explanations, information withholding is influenced by the behaviors of peers as well as the attitudes of superiors in the profession. We discuss the implications for the professions literature, theories of organizational learning, and knowledge management initiatives in firms.